Sustained Antibiotic-Eluting Intra-Ocular Lenses: A New Approach - Tan, Dulcia Wei Ni (2017)
Currently, infections following cataract surgery are not as effectively managed with antibiotic eye drops, which suffer from poor bioavailability of drug and low patient compliance. The ideal solution, which can help to overcome the issue of drug wastage and poor bioavailabilty, as well as the need for frequent applications (patient inconvenience), is a drug-eluting intraocular lens (IOL). We describe a novel approach to such a drug-eluting lens by using a peripheral IOL attachment as a drug depot to deliver antibiotics, Levofloxacin (LFX) or Moxifloxacin (MFX). In this work, drug was entrapped within a fully-degradable polymer, poly(L-lactide-co-ɛ-caprolactone) (PLC). The effects of drug loading and solvent type on drug release and film morphology were investigated using cast films. The study clearly demonstrated that a slower-evaporating solvent tetrahydrofuran (THF) resulted in a better surface morphology, as well as lower initial burst compared to dichloromethane (DCM), and hence, was better suited to developing a drug-eluting attachment with sustained release of drug. When attachments were fabricated with drugs at high loading percentages (20% and 25% in polymer), significant burst was observed compared to films: this is attributed to the higher surface-to-volume ratio of the attachments. When the levofloxacin (LFX) loading percentage was decreased to 3% and 5%, the attachments presented lower burst and sustained release with therapeutic efficacy. This work has demonstrated the potential of using an IOL attachment as a more efficacious anti-infective option compared to daily eye drops.